Diabetes mellitus progression exacerbates post-stroke damage and diminishes the efficacy of urokinase - Shaojun Liu; Jiawei Huang; Tingting Yu; Valery V. Tuchin; Dongyu Li; Dan Zhu (Journal of Innovative Optical Health Sciences, 2026)
Stroke is a leading cause of global mortality, and diabetes mellitus (DM) is an independent risk factor for ischemic stroke. Although longer DM duration is associated with increased stroke risk, how disease progression influences post-stroke pathology and thrombolytic efficacy remains poorly understood. This study investigated the impact of different durations of DM on vascular structure and function after an ischemic stroke, as well as the efficacy of urokinase thrombolysis in male streptozotocin-induced type 1 diabetic mice. Our findings demonstrate that DM significantly exacerbates the pathological damage following an ischemic stroke, worsening with longer disease progression. In four-week diabetic mice, spontaneous cerebral blood flow recovery capability was reduced, infarct volume increased, vascular structures exhibited compensatory yet dysfunctional changes, and neurological deficits worsened. Furthermore, the therapeutic efficacy of urokinase decreased with prolonged DM, becoming ineffective in four-week diabetic mice. These findings provide critical experimental evidence for optimizing individualized thrombolytic strategies in stroke patients with comorbid DM. It should be noted that this work only includes male mice with type 1 diabetic model, these findings require further validation in female animals and type 2 diabetic model before broad clinical translation.